(untitled) (Tanzania Medical Journal, 2025)
Melanoma is a malignancy of melanocytes and can present anywhere in the body where there are melanocytic cells. Cutaneous melanoma is the third cutaneous cancer, but it is the most fatal. Cutaneous melanoma metastasizes widely; the commonest sites of metastasis are the lungs, skin, subcutaneous tissue, liver, brain, and bone. Rarely, metastasis can involve the orbit, and even more rarely, it can be the first presentation of widespread systemic metastasis. Orbital metastases from cutaneous melanoma typically occur at a late stage of the disease, where it carries a poor survival rate. We report a 68-year-old woman, who presented with a 3-month history of right eye protrusion accompanied by vision loss. She reports having a non-healing black swelling on her left big toe, for which she underwent amputation a year ago. The amputated toe was not taken for histopathology examination. On ocular examination, a brownish-pigmented protruding mass that appeared to originate from both superior and inferior conjunctival fornices, pushing the eyeball laterally, with tortuous feeder vessels and an opaque cornea, was seen. Hyperpigmented skin nodules on the left foot and an ulcer on the anteromedial aspect of the left leg were seen. A histopathology examination of the skin nodule revealed a cutaneous melanoma (Clarks level VI) with positive margins. The patient underwent orbital exenteration, and the biopsy was conclusive for a metastatic malignant melanoma of the orbit. Unfortunately, skin melanomas can mimic other benign skin lesions, making it easy to miss or delay diagnosis, which can lead to a poor survival outcome. The patient missed an opportunity for an early diagnosis of skin melanoma due to a lack of histopathological examination of the amputated toe, probably due to a low index of suspicion. To avoid delays in treatment, efforts should be made to do histopathology studies for every excised lesion, even in low-resource settings.